2020
DOI: 10.3389/fpsyg.2020.582578
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Emotional Intelligence and the Intention to Use Cannabis in Spanish Adolescents: Influence of COVID-19 Confinement

Abstract: The disease brought about by the SARS-CoV-2, COVID-19 coronavirus has had an unprecedented global impact. Confinement to control the outbreak may have mental health consequences for the most vulnerable in the population, including adolescents. This study aims to describe and analyze the relationships between the stress variables, Emotional Intelligence and the intention to use cannabis in healthy adolescents, before and after the end of the COVID-19 pandemic containment stage. A comparative correlational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 41 publications
1
34
0
2
Order By: Relevance
“…A proportion of studies ( n = 10, 2,321) utilised interviews, of which some were parent interviews ( n = 2, 535), some were child interviews (n = 5, 2,629), and some interviewed both parents and children ( n = 3, 261). Duration of lockdown was 52.3 ± 21.3 days in the included studies (range 30 [ 1 , 4 , 12 , 17 , 25 , 27 , 34 , 39 , 41 , 57 , 82 ]—100 days [ 80 , 100 ]). The characteristics of the included studies and their findings are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A proportion of studies ( n = 10, 2,321) utilised interviews, of which some were parent interviews ( n = 2, 535), some were child interviews (n = 5, 2,629), and some interviewed both parents and children ( n = 3, 261). Duration of lockdown was 52.3 ± 21.3 days in the included studies (range 30 [ 1 , 4 , 12 , 17 , 25 , 27 , 34 , 39 , 41 , 57 , 82 ]—100 days [ 80 , 100 ]). The characteristics of the included studies and their findings are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…There were also significant differences seen regarding mood symptoms ( p < .01). Children in the northern areas were sadder ( p < 0.001) and more bored ( p < 0.01) in comparison to children in central areas Liebana-Presa et al 2020 [ 57 ] Spain Cross-sectional 300 62 14.0 ± 1.0, 13–17 ★★ There was a strong correlation between the physiological and emotional manifestations in stress (r = 0.778). Regarding the intention to use cannabis, the component of attitude toward its use is significantly correlated with stress: emotional manifestations (r = 0.260), physiological ( r = 0.300) and behavioural ( r = 0.412) Liu et al 2020 [ 59 ] China Cross-sectional 1264 44% 9.8, 7–12 Y N.A Amongst children, prosocial behaviours prevalence was 10.3%, followed by conduct problems (7.0%), peer problems (6.6%), hyperactivity-inattention (6.3%) and emotional problems (4.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies targeted primary school populations (<12 years) (Alonso-Mart ınez et al, 2021; Chen, Chen, et al, 2020; de Avila et al, 2020;Dumas, Ellis, & Litt, 2020;Fontenelle-Tereshchuk, 2020;A. Gassman-Pines et al, 2020;Glynn, Davis, Luby, Baram, & Sandman, 2021;Lee, Ward, Chang, & Downing, 2021;Romero, L opez-Romero, Dom ınguezalvarez, Villar, & G omez-Fraguela, 2020;Waller et al, 2021;Xie et al, 2020;Xue et al, 2021), 27 reported on middle and high school populations (aged 12-18) (Alamrawy et al, 2021;Breaux et al, 2021;Buzzi et al, 2020;Cao et al, 2021;Chi et al, 2021;Ellis, Dumas, & Forbes, 2020;Fish et al, 2020;Giannopoulou, Efstathiou, Triantafyllou, Korkoliakou, & Douzenis, 2021;Janssen et al, 2020;Kılınc ßel, Kılınc ßel, Muratda gı, Aydın, & Usta, 2020;Li et al, 2021;Liebana-Presa et al, 2020;Lu et al, 2020;Luthar, Ebbert, & Kumar, 2020;Magson et al, 2021;Masuyama, Shinkawa, & Kubo, 2020;Murata et al, 2021;Oosterhoff, Palmer, Wilson, & Shook, 2020;Pons et al, 2020;Qi, Liu, et al, 2020;Qi, Zhou, et al, 2020;Rauschenberg et al, 2020;Rogers et al, 2021;Scott et al, 2021;Secer & Ulas, 2020;…”
Section: Age Distributionmentioning
confidence: 99%
“…A higher perceived ability to regulate emotions was related to a lower frequency of cannabis use in other studies with adolescents [ 39 , 40 ]. On the other hand, a high level of attention to emotions has been linked to a higher level of stress, which hinders the ability to understand and regulate emotions and increases the probability of cannabis use in adolescents [ 41 ]. In terms of EI evaluated through maximum performance tests, the few existing studies such as the one carried out by Brackett, Mayer, and Warner [ 42 ], showed significant negative relations between the components of emotional perception, emotional facilitation, emotional understanding, and emotional regulation regarding the frequency of cannabis use in university students.…”
Section: Introductionmentioning
confidence: 99%